(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of individual characteristics, promotion and organizational culture simultaneously on employee performance at the Office of BPJS Ketenagakerjaan, Bali Gianyar Branch. The number of samples in this study were 40 respondents, which were determined using the saturated method. The research data was collected through observation, documentation, interviews, and questionnaires where the research data was processed using multiple linear regression analysis techniques. Based on the results of the study, the results obtained, individual characteristics, promotions and organizational culture partially and simultaneously have a positive and significant effect on employee performance at the Office of BPJS Ketenagakerjaan Bali Gianyar Branch. The magnitude of the influence of the independent variable on employee performance at the Office of BPJS Employment Bali Gianyar Branch is 58.8%.